An integrated modeling framework for crop and biofuel systems using the DSSAT and GREET models. (October 2018) - Anderson, Ryan; Keshwani, Deepak; Guru, Ashu; Yang, Haishun; Irmak, Suat; Subbiah, Jeyamkondan
Abstract: As global demand for food, energy, and water resources continues to increase, decision-makers in these sectors must find sustainable ways to produce and provide for the growing population. While many models have been created to aid in decision-making in these systems, there is a lack of robust integrated models that enable an understanding of the interconnections of these systems. This study develops a modeling framework that explores the connections of the corn and ethanol systems, two major food and energy resources. A crop modeling tool (DSSAT) and a biofuel life cycle assessment tool (GREET) are connected using a service-oriented architecture programming approach. A Python program is developed to connect these two models and run scenario analyses to assess environmental impacts of the integrated system. This paper explores the impact of decisions such as fertilizer use and plant population on environmental effects of greenhouse gases, energy use, and water in the integrated system. Highlights: Service-oriented architecture to integrate models for crop production and biofuel life cycle assessment. Development and connection of wrappers for DSSAT and GREET models. Sensitivity and scenario analyses on integrated model for decision support.